Associations between paracetamol (acetaminophen) intake between 18 and 32 weeks gestation and neurocognitive outcomes in the child: A longitudinal cohort study. Issue 3 (15th September 2019) - Golding, Jean; Gregory, Steven; Clark, Rosie; Ellis, Genette; Iles‐Caven, Yasmin; Northstone, Kate
Abstract: Background: The majority of epidemiological studies concerning possible adverse effects of paracetamol (acetaminophen) in pregnancy have been focussed on childhood asthma. Initial results of a robust association have been confirmed in several studies. Recently, a few cohort studies have looked at particular neurocognitive outcomes, and several have implicated hyperactivity. Objectives: In order to confirm these findings, further information and results are required. Here, we assess whether paracetamol intake between 18 and 32 weeks gestation is associated with childhood behavioural and cognitive outcomes using a large population. Methods: Data collected by the Avon Longitudinal Study of Parents and Children (ALSPAC) at 32 weeks gestation and referring to the period from 18 to 32 weeks, identified 43.9% of women having taken paracetamol. We used an exposome analysis first to determine the background factors associated with pregnant women taking the drug, and then allowed for those factors to assess associations with child outcomes (measured using regression analyses). Results: We identified 15 variables independently associated with taking paracetamol in this time period, which were used as potential confounders. Of the 135 neurocognitive variables considered, adjusting for the likelihood of false discovery, we identified 56 outcomes for adjusted analyses. Adjustment identified 12 showing independent associations with paracetamol use at P < .05, four of which were at P < .0001 (all related to child behaviours reported by the mother at 42 and 47 months; eg conduct problems: adjusted mean score + 0.22 (95% confidence interval 0.10, 0.33)). There were few associations with behavioural or neurocognitive outcomes after age 7‐8 years, whether reported by the mother or the teacher. Conclusions: If paracetamol use in mid‐to‐late pregnancy has an adverse effect on child neurocognitive outcome, it appears to mainly relate to the pre‐school period. It is important that these results be tested using other datasets or methodologies before assuming that they are causal.